1987
DOI: 10.1104/pp.84.3.906
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Soybean Nitrogen Fixation in Response to Rhizosphere Oxygen

Abstract: ABSTRACINodule nitrogen fixation rates are regulated by a mechanism which is responsive to the rhizosphere oxygen concentration. In some legumes, this oxygen-sensitive mechanism appears to involve changes in the gas permeability of a diffusion barrier in the nodule cortex. In soybean evidence for such a mechanism has not been found. The purpose of this research was to make quantitative measurements of soybean nodule ps permeability to test the hypothesis that soybean nodule gas permeability is under physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…A decrease in permeability following an increase in 0e has previously been reported (9,23 (Fig. 3A).…”
Section: Relationship Between Permeability and Vmaxsupporting
confidence: 78%
See 1 more Smart Citation
“…A decrease in permeability following an increase in 0e has previously been reported (9,23 (Fig. 3A).…”
Section: Relationship Between Permeability and Vmaxsupporting
confidence: 78%
“…Similar permeability changes occur in response to acetylene exposure (12) or with increased or decreased external 02 concentration (23,27). Studies with microelectrodes (19,27) and theoretical considerations (18) suggest that nodule permeability is limited mainly by one or more layers of tightly packed cells in the nodule cortex.…”
mentioning
confidence: 80%
“…Indeed, estimates of nodule permeability made by the method of Sheehy et al (19) are based on nodule respiration rate. It should also be noted that changes in nodule permeability to acetylene (9) and ethylene (25), neither of which is carried by Lb, parallel changes in nodule permeability to 02 (Table III). For the flooded interior case, Vmax was estimated correctly, but the other two parameters were not.…”
Section: Oxygen Concentrations In the Central Zonementioning
confidence: 83%
“…The low solubility of 02 in water or cytoplasm further decreases the diffusion rate in cells relative to air. It has been suggested that changes in either the radius (19,25) or the number (1 1) of open pores could control permeability. Under the variable plug thickness hypothesis (1 1), each pore contains a plug of water, and permeability depends on the thickness of the plug.…”
mentioning
confidence: 99%
See 1 more Smart Citation